Duszpasterstwo młodzieży w Niemczech: „Evergreen” z zawsze nowymi aspektami - Kießig, Sebastian (Studia Pastoralne, 2026)
In Germany, the youth ministry is a thematic field that is reflected in various different ways since the time of the Second Vatican Council. This paper responds to these different types of reflections and develops a few pastoral-theological accesses. The German dioceses adopted on the Synod of Würzburg (1971 to 1975) a resolution about aims and assignments of the youth ministry of the Church. In 1991 the German Conference of Bishops publishes leading guidelines for the youth ministry. The aim of both papers of the Church is to lay the foundations of a theory of the youth ministry. This theory should be of good service to the practical pastoral service. Its theological foundations include anthropological (adolescents and young adults are the subject of the youth ministry), ecclesiological (the pastoral service is nourished by the act of being sent, i.e. its mission) and christological (God’s work is directly performed in the lives of young people). This paper reflects about this theology in an exemplary way by discussing three cases: First, it contemplates the service of altar servers in German parishes; second, it treats the theory of the school ministry and, third and finally, it deals with the pastoral activities of a spiritual community.